MODERNISASI SISTEM PEMASYARAKATAN SEBAGAI SUB SISTEM PERADILAN PIDANA DI INDONESIA (STUDI ANALISIS SIYASAH QADHA’IYAH SYAR’IYAH) - Edi Rosman; Zul Efendi; Saiful Amin; Miswardi Miswardi (Ensiklopedia of Journal, 2021)
The panitentiary System in Indonesia in general and in West Sumatra in particular is a sub-Criminal Justice System. Goal orientation of the criminal process since the police, prosecutors, judiciary is a panitentiary. The philosophy’s is conceptually much different from the concept of imprisonment. The existence of a gap between the conceptual ideal and its practical reality, the  planning and implementing the modernization process of both the system and the penitentiary itself. Penitentiary is "a place to the development of prisoners, panitentiary students, and  clients." The implementation its system is essentially an effort to develop Indonesian people as a whole, so that in this context prisons have a very strategic role in the context of fostering human resources, the implementation of guidance for panitentiary including how to create conducive conditions in carrying out duties. The effective coaching in prisons to develop Indonesian people as a whole is very important for modernization. In general, prisons in historical contexts often prioritize a security approach, whether it is maximum security, medium security and minimum security. Modernization is security approach and spiritual approach when integreted sistem. In perspektive siyasah qadha’iyah’s is the essence of the modernization of the prison system now and in the future.Keywords: Panitentiary System;Modernization; siyasa qadha'iyah Syar'iyah